(untitled) (Jurnal Online Pertanian Tropik, 2017)
Molecular variance is very important. The information resulted from the analysis at the molecular level can advantage as a first step to manage breeding programs. The aim of this research was to determine a molecular variance in palm oil-based on SSR primer using FR0465, FR391, FR304, FR0350 and FR3693 primers. The research was conducted at Terpadu Laboratory, Faculty of Medicines, North Sumatera University from September 2015 to February 2016. Gen Alex ver. 6.501, Power Marker 3.25 and software DARwin Software Version 6 was used to calculate and analysis. The result of this research showed that the value of molecular variants of Palm Oil (E. guineensis) was 62.43%, polymorphic information content (PIC) was 0.338. The measure of fragment about 120 bp – 496 bp. FR02350 has the highest number of alel and the value of expected heterozygote (He) was 0.685.